Cheese fortification using saturated monoglyceride self‐assembly structures as carrier of omega‐3 fatty acids. (22nd June 2015) - Calligaris, Sonia; Ignat, Alexandra; Biasutti, Marialuisa; Innocente, Nadia; Nicoli, Maria Cristina
Summary The purpose of this research was to study the capacity of emulsions containing saturated monoglyceride self‐assembly structures to deliver omega‐3 fatty acids in fresh soft cheese. To this aim, fortified emulsions containing different ratios of milk, saturated monoglycerides (MGs) and cod liver oil were added to milk before cheese‐making. These emulsions were characterised by distinct microstructural features observed by polarised light microscopy and apparent viscosity values. The omega‐3 delivery performance of MG emulsions highlighted that this strategy allowed a good retention of the omega‐3‐rich oil in the curd (up to 75%). The fortified cheeses showed yield value and fat content higher than those of control samples. The enriched cheese showed hardness and cohesiveness obtained by texture profile analysis similar to those of the unfortified product. Only a slight decrease in gumminess was detected in fortified cheese.